2017
DOI: 10.1177/2192568217700115
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Delirium After Spine Surgery in Extremely Elderly Patients Aged 80 Years or Older and Review of the Literature: Japan Association of Spine Surgeons with Ambition Multicenter Study

Abstract: Study Design:Retrospective database analysis.Objective:Spine surgeries in elderly patients have increased in recent years due to aging of society and recent advances in surgical techniques, and postoperative complications have become more of a concern. Postoperative delirium is a common complication in elderly patients that impairs recovery and increases morbidity and mortality. The objective of the study was to analyze postoperative delirium associated with spine surgery in patients aged 80 years or older wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 65 publications
2
56
0
3
Order By: Relevance
“…In our study, there were 8 patients (2.6%) who were diagnosed early (the rst 3 postoperative days). This rate is consistent with the reported rates of patients who were diagnosed with POD in literature (25). Moreover, the data obtained from the risk factors we investigated and the risk factors due to patients, surgery or anesthesia were consistent with literature.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, there were 8 patients (2.6%) who were diagnosed early (the rst 3 postoperative days). This rate is consistent with the reported rates of patients who were diagnosed with POD in literature (25). Moreover, the data obtained from the risk factors we investigated and the risk factors due to patients, surgery or anesthesia were consistent with literature.…”
Section: Discussionsupporting
confidence: 91%
“…The predisposing factors are the patient's basic vulnerabilities including age, antipsychotic medication use, smoking status, impaired ability to complete activities of daily living, history of delirium, weakness, and cognitive impairment 18 . Precipitating (or accelerating) factors occur during hospitalization, including massive bleeding during surgery, 19 opioid use, 19,20 or postoperative fever 21 . However, because of the heterogeneity of available studies with respect to the type of surgery, age group, and risk factors, it is difficult to draw conclusions about the most important risk factors for delirium.…”
mentioning
confidence: 99%
“…However, the study had several limitations including that researchers did not consider specific age groups or include information on a subgroup of adults older than 65 years. Moreover, a re‐analysis of the data would permit the inclusion of observational studies 19,20,23 that have become available since the publication of the meta‐analysis.…”
mentioning
confidence: 99%
“…11 Kobayashi et al identified that cervical lesion surgery and an EBL greater than 300 ml were significantly associated with postoperative delirium in patients 80 years or older. 17 Surgeons should pay careful attention when performing surgery in elderly patients who cannot accept a transfusion due to religious reasons and in patients with risk factors for postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%